The ecology of Aedes aegypti and Aedes albopictus larvae habitat in coastal areas of South Sulawesi, Indonesia - ARINI RATNASARI; ARIF RAHMAN JABAL; NUR RAHMA; SRI NUR RAHMI; MILA KARMILA; Isra Wahid (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Ratnasari A, Jabal AR, Rahma N, Rahmi SN, Karmila M, Wahid I, 2020. The ecology of Aedes aegypti and Aedes albopictus larvae habitat in coastal areas of South Sulawesi, Indonesia. Biodiversitas 21: 4648-4654. Aedes aegypti and Aedes albopictus are arbovirus vectors that can adapt to various environmental conditions. This study aimed to analyze the spatial distribution, habitat characteristics, and the correlation between the number of Ae. aegypti and Ae. albopictus larvae with physical factors. The larvae were collected from seven sampling locations along the coast of South Sulawesi at a distance of 100 m, 500 m, 1 km, and 2 km from the coastline. The collected samples and their water habitat were examined in the Entomology Laboratory of the Faculty of Medicine, Hasanuddin University, South Sulawesi, Indonesia. The number of larvae was counted (3182 larvae of both kinds), and the pH and salinity of the water were measured. Data analysis was performed with IBM SPSS version 24 and spatial distribution of larvae was mapped with ArcGIS version 10.5. We found that the highest number of Ae. aegypti was at a distance of 100 m from the coastline (73.34%), while Ae. albopictus was at 500 m (34.14%). Most of the mosquitos laid their eggs on discarded boats as observed in the Kurri Caddi coast (31.2%). The observed ranges of pH, salinity, and temperature of larvae habitat were 5.5-6.4, 5-2 ppt, and 28-31°C, respectively. The total number of larvae had a significant correlation p<0.05 with the physical factors, i.e., distance from the coastline, water pH, temperature, and kind of water storages (containers). This study showed that physical factors in the coastal area significantly influenced the habitat characteristics and the abundance of Ae. aegypti and Ae. albopictus larvae.